Brane expansions for anti-symmetric line operator index - Yosuke Imamura; Masato Inoue (Journal of High Energy Physics)
Abstract Based on the D5-brane realization of Wilson line operators in anti-symmetric representations, we propose brane expansion formulas for I N,k , the Schur index of N $$ \mathcal{N} $$ = 4 U(N) SYM decorated by line operators in the anti-symmetric representation of rank k. For the large N index I ∞,k we propose a double-sum expansion, and for finite N index I N,k we propose a quadruple-sum expansion. Objects causing finite k and finite N corrections are disk D3-branes ending on the D5-brane.